The effect of reactor configuration on bioelectrochemical production of acetate from carbon dioxide - Karinsalo, Janniina (My University, 2020)
To mitigate global warming and its adverse effects, more sustainable alternatives for the fossil fuel-based production of energy and chemicals are needed. Acetogenic bacteria can reduce the greenhouse gas CO2 into hydrocarbons like acetate using reducing equivalents supplied via a cathode in a bioelectrochemical system. However, the production process needs improvements to enable cost-effective production in an industrial scale. To improve the process, a fluidized bed reactor (FluBR) was tested to enhance mass transfer. The tubular cathode chamber inside the cylindrical anode chamber hosted a mixed culture of acetogens and activated carbon granules, which were fluidized at a flow rate of 170 mL/min. As a control for fluidization, a fixed bed reactor (FixBR) was prepared by replacing the bed material with heavier graphite granules, while the flow rate was 250 mL/min. Both reactors supported bioelectrochemical production of acetate reaching their peak performance 14 days after the acetate production had started. The maximum volumetric productivity was 0.21 g/L/d in the FluBR and 0.22 g/L/d in the FixBR while 37 % and 40 % of the electrons provided by the cathode were assimilated into acetate in the FluBR and the FixBR, respectively. The performance of the FixBR and the FluBR were similar, but the differences between the reactor setups could have affected the results. The reactors need to be further tested for comparable results and optimized to improve the acetate production.

Ilmastonmuutoksen ja sen haittavaikutuksien vähentämiseksi tarvitaan kestävämpiä vaihtoehtoja fossiilisille polttoaineille ja kemikaaleille. Mikrobielektrosynteesissä asetogeeniset bakteerit käyttävät katodilta saatuja elektroneja hiilidioksidin pelkistämiseen muodostaen hiilivetyjä kuten asetaattia. Jotta menetelmää voitaisiin käyttää kustannustehokkaasti teollisessa mittakaavassa, tuottoprosessia pitäisi parantaa. Työn tarkoitus oli parantaa mikrobielektrosynteesin tehokkuutta parantamalla massansiirtoa leijupetireaktorin avulla. Reaktorin sylinterimäisen anodikammion sisällä oli putkimainen katodikammio, jossa kasvatettiin asetogeeneja sisältävää sekaviljelmää. Katodikammioon lisättiin aktiivihiilirakeita, joita leijutettiin 170 ml/min virtausnopeudella. Leijupetireaktorin kontrollina käytettiin muuten samanlaista kiintopatjareaktoria, jossa aktiivihiilirakeiden sijaan käytettiin raskaampia grafiittirakeita, joiden läpi kasvatusmediumia kierrätettiin 250 ml/min virtausnopeudella. Molemmat reaktorit tukivat asetaatin biosähkökemiallista muodostusta saavuttaen suurimmat tuottonsa ja tehokkuutensa 14 päivää asetaatin tuoton alkamisen jälkeen. Suurin volumetrinen tuottavuus oli 0.21 g/L/d leijupetireaktorissa ja 0.22 g/L/d kiintopatjareaktorissa. Lisäksi leijupetireaktorissa enimmillään 37 % ja kiintopatjareaktorissa enimmillään 40 % katodilta saaduista elektroneista hyödynnettiin asetaatin tuottoon. Reaktorien tulokset olivat lähes samanlaiset, mutta reaktorien väliset erot esimerkiksi virtausnopeudessa ovat voineet vaikuttaa tuloksiin. Reaktoreita tulisi siis tutkia ja kehittää edelleen vertailukelpoisempien tulosten sekä parempien tehokkuuksien ja tuottavuuksien saavuttamiseksi.
Keywords: Bioelectrochemical system, Biological fluidized bed, Mixed reactor microbiome, Acetogenesis